Modelagem e avaliação numérica de absorvedores dinâmicos de vibrações sintonizáveis baseados em ligas com memória de forma - Paulo Júnior, Wellington Luziano (2012)
In the context of the so-called smart materials, shape memory alloys (SMA) have been extensively investigated aiming at various applications in different types of engineering prob- lems as well as interdisciplinary problems. Specifically, SMAs have been used for the mitiga- tion of mechanical vibrations, owing to their characteristic pseudoelastic effect, which is re- sponsible for the occurrence of hysteresis. Another relevant feature of these materials is the coexistence of two crystallographic phases (martensite and austenite), which have dissimilar mechanical properties, whose relative fractions depend on temperature and stress. In the present dissertation, this latter feature is explored in association with a strategy of passive vibration control which is based on tunable dynamic vibration absorbers (TDVA). These de- vices, once connected to a vibrating structure, can have their inertia and/or stiffness and/or damping adjusted to match the excitation frequency. Specifically, such tuning is achieved by controlling the martensite/austenite fraction by applying convenient thermal loads. By means of numerical simulations, which include the integration of the equations of motion, it is put in evidence the possibility of tuning a TDVA applied to a single degree-of-freedom system, with- in a given frequency band using two configurations of the resilient element (SMA rod and helicoidal spring). The results enable to evaluate the levels of vibration mitigation achieved and confirm that the strategy investigated can provide improved performance in terms of vibration attenuation.